Modified coir pith with glucose syrup as a supporter in non-external nutrient supplied biofilter for benzene removal by Bacillus megaterium - Dolphen, Rujira (Environmental technology, 2020)
Coir pith glucose syrup beads were used as a supporter in a biofilter system. The modified coir pith beads provided a carbon source and controlled humidity for microorganism growth for long-term operation without external nutrient supplementation. For the screening, Bacillus spp. were immobilised on coir pith beads and used for benzene bioremediation. The result showed that coir pith beads immobilised with Bacillus megaterium can remove on average 85-100% of the benzene (215-day operation). In addition, B. megaterium presented the ability to transform benzene to catechol. For an up-scaled application, a 25-L biofilter system was developed and tested in a closed 24-m3 container re-injected with 0.6 ppm benzene for 8 cycles. The system presented the ability to remove 100% of the benzene. This biofilter has the potential to be applied in a real benzene-contaminated site